Students’ perceptions and motivation in learning second language acquisition for future English teachers - Novinda, Kushardiyanti; Novinda, Daud Jiwandono; Novinda, Khairiyah Eka Januaristi (ELT Forum: Journal of English Language Teaching, 2025)
This article explores students’ perceptions and motivations of English education students in learning Second Language Acquisition (SLA) material, particularly in the context of their future roles as English teachers. This study investigates how students’ motivation and perception evolve when taking a Second Language Acquisition (SLA) course, often undertaken without a clear understanding of its content. Key factors influencing students' engagement with SLA material are identified. It examines the relationship between motivation and perceived relevance of the content in the material and highlights the implications for teacher education programs. Drawing from students’ voices in teacher education programs in Indonesia, the research follows their journey from initial confusion to newfound understanding and appreciation for SLA content. Significant correlations are revealed between students’ motivation level and their perception of the material’s applicability to their future teaching career. Using a qualitative approach based on interviews and thematic analysis, this study reveals how self-efficacy, aspirations to become teachers, and instructor support play pivotal roles in shaping students’ evolving views. The findings reveal significant correlations between students' motivation levels and their perceptions of SLA material's applicability to their future teaching careers. Practical suggestions for enhancing SLA curriculum delivery in teacher education programs are provided. This study addresses a critical gap in the literature concerning the specific motivations and perceptions of future English teachers in the SLA context.